Computing in the composite "GF(qm)" of characteristic 2 formed by means of an irreducible binomial - Kościelny, Czesław (Zielona Góra: Uniwersytet Zielonogórski)
Since the operation of reduction modulo a polynomial needed for parallel computing in "GF(qm)" is the simplest possible in the case of a binomial, in this paper the main properties of irreducible binomials over GF(q) of characteristic 2 are given.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka